Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
PURPOSE: STAT3 is important in promoting a pro-oncogenic tumor microenvironment. This first randomized trial of a STAT3-targeting ASO with pembrolizumab assessed whether this first-line combination would improve outcomes compared with pembrolizumab alone in recurrent/metastatic (R/M) head and neck squamous cell carcinoma (HNSCC). PATIENTS AND METHODS: This multicenter, randomized, open-label, controlled study (NCT05814666) enrolled patients with previously untreated R/M-HNSCC with positive PD-L1 expression (combined positive score [CPS] ≥1). Patients were stratified by CPS (1-19; ≥20) and randomized 2:1 to danvatirsen 3mg/kg IV weekly (with 2 loading doses in week 1) plus pembrolizumab 200mg IV every 3 weeks or pembrolizumab alone. Patients received 21-day treatment cycles until progressive disease, unacceptable toxicity, or voluntary withdrawal. Primary endpoint was overall response rate (ORR: partial + complete response per RECIST-v1.1). RESULTS: 69 patients were randomized and 66 treated (51 [77.3%] male), 45 with danvatirsen + pembrolizumab, 21 with pembrolizumab alone. Enrolment was stopped due to lack of response in the CPS 1-19 cohort after ≥1 scan (~6 weeks of treatment) and in the CPS ≥20 cohort after ≥2 scans (~12 weeks). In the final analysis, ORRs were 15.6% and 14.3%, respectively (risk difference 1.3, P=1.0). The treatment-emergent adverse-event rate was increased in the combination arm (97.8% vs 85.7%), and the combination side effect profile was similar to previous danvatirsen studies. CONCLUSIONS: Combination danvatirsen + pembrolizumab did not improve ORR compared to pembrolizumab alone in first-line treatment of R/M-HNSCC. Further exploration of STAT3-targeted approaches is needed within the context of immunotherapy.